Uganda: Lawyers go digital to reach women farmers - Bafana, Busani (Technical Centre for Agricultural and Rural Cooperation, 2019)
For less than 1, women farmers in Uganda are accessing legal advice via their mobile phones. The SMS service, driven by an all-female team under the leadership of Hellen Mukasa, helps women to realise and defend their rights, particularly in regards to land ownership.